Temperament structure and ways of coping with stress among professional soccer and basketball players - Blecharz, J.; Siekanska, M. (Biology of Sport, 2007)
The temperamental traits play a crucial role in the process of the adjustment of an individual to the requirements of the environment: at school, at work and, of course, in sport activity. In the research on stress, temperament has the status of a moderator (i.e. a condition preceding a given phenomenon in time) that modifies stressors, the state of stress, the ways of coping with stress, and the consequences of the state of stress. The purpose of this study was to investigate and describe relations between temperament structure and ways of coping in stressful situations. The subjects - 104 top level athletes (54 soccer players and 50 basketball players) - completed "The Formal Characteristics of Behaviour - Temperament Inventory" (FCB - TI) by B. Zawadzki and J. Strelau and "The Coping Inventory for Stressful Situations" (CISS) by N. S. Endler and J .D. A. Parker. Results indicate that there is significant relationship between the temperamental traits and the ways of coping especially in case of Emotion-Oriented Coping that correlates with Briskness (r=-0.41, p=0.01), Perseverance (r=0.47, p=0.01), Sensory Sensitivity (r=-0.24, p-0.05), Emotional Reactivity (r=0.64, p=0.01) and Endurance (r=-0.47, p=0.01). Avoidance-Oriented Coping correlates with Activity (r=0.28, p=0.01). Task-Oriented Coping correlates with Briskness (r=0.25, p<0.05), Emotional Reactivity (r=-0.23, p<0.05) and Endurance (r=0.20, p=0.05). The results indicate that the temperamental traits can be important predictors of the style of coping with stress.